Challenges in the Discovery and Optimization of mGlu(2/4) Heterodimer Positive Allosteric Modulators - Fulton, Mark Gallant (Lett Drug Des Discov, 2019)
BACKGROUND: This article describes the challenges in the discovery and optimization of mGlu2/4 heterodimer Positive Allosteric Modulators (PAMs). METHODS: Initial forays based on VU0155041, a PAM of both the mGlu4 homodimer and the mGlu2/4 heterodimer, led to flat, intractable SAR that precluded advancement. Screening of a collection of 1,152 FDA approved drugs led to the discovery that febuxostat, an approved xanthine oxidase inhibitor, was a moderately potent PAM of the mGlu(2/4) heterodimer (EC(50) = 3.4 μM), but was peripherally restricted (rat K(p) = 0.03). Optimization of this hit led to PAMs with improved potency (EC(50)s <800 nM) and improved CNS penetration (rat Kp >(2), an ~100-fold increase). RESULTS: However, these new amide analogs of febuxostat proved to be either GIRK1/2 and GIRK1/4 activators (primary carboxamide congeners) or mGlu(2) PAMs (secondary and tertiary amides) and not selective mGlu(2/4) heterodimer PAMs. CONCLUSION: These results required the team to develop a new screening cascade paradigm, and exemplified the challenges in developing allosteric ligands for heterodimeric receptors.